Elucidating the impact of A-site cation change on photocatalytic H2 and O2 evolution activities of perovskite-type LnTaON2 (Ln = La and Pr). Issue 33 (11th August 2017) - Hojamberdiev, Mirabbos; Bekheet, Maged F.; Hart, Judy N.; Vequizo, Junie Jhon M.; Yamakata, Akira; Yubuta, Kunio; Gurlo, Aleksander; Hasegawa, Masashi; Domen, Kazunari; Teshima, Katsuya
Abstract : Impact of A-site cation change on photocatalytic H2 and O2 evolution of LnTaON2 (Ln = La and Pr) was studied. Abstract : Transition metal (oxy)nitrides with perovskite-type structures have been regarded as one of the promising classes of inorganic semiconductor materials that can be used in solar water splitting systems for the production of hydrogen as a renewable and storable energy carrier. The performance of transition metal (oxy)nitrides in solar water splitting is strongly influenced by the crystal structure-related dynamics of photogenerated charge carriers. Here, we have systematically assessed the influence of A-site cation exchange on the visible-light-induced photocatalytic H2 and O2 evolution activities, photoanodic response, and dynamics of photogenerated charge carriers of perovskite-type LnTaON2 (Ln = La and Pr). The structural refinement results reveal the orthorhombic Imma and Pnma structures for LaTaON2 and PrTaON2, respectively; the latter has a more distorted crystal structure from the ideal cubic perovskite due to the smaller size of Pr 3+ cations. Compared with LaTaON2, PrTaON2 exhibits lower photocatalytic H2 and O2 gas evolution activities and photoanodic response owing to an excessive amount of intrinsic defects associated with anionic vacancies and reduced tantalum species stemming from a long high-temperature nitridation process under reductive NH3 atmosphere. Transient absorption signals evidence the faster decay of photogenerated electrons (holes) in Pt (CoO x )-loaded LaTaON2 than that in Pt (CoO x )-loaded PrTaON2, consistent with the photocatalytic and photoelectrochemical performance of the two photocatalysts. This study suggests that in addition to selecting a suitable A-site cation, it is prerequisite to synthesize LnTaON2 (Ln = La and Pr) crystals with a low defect density to improve their photo-conversion efficiency for solar water splitting.